Baseline study on condom usage, safe sexual practices and sexually transmitted diseases among men and women aged 15-60 years in Orange Farm, South Africa 2002: A retrospective analysis - Awuonda, George Otieno (My University, 2008)
Abstract: Background: The global estimated adult and child deaths from HIV/AIDS in 2006 were 2.9 million and those living with HIV stood at 39.5 million. Of the HIV deaths, 72% (2.1 million) occurred in Sub-Saharan Africa (SSA). Two thirds (63%) of all adults and children with HIV globally live in, with its epicenter in Southern Africa. One third (32%) of all people with HIV globally live in Southern Africa and 34% of all deaths due to AIDS in 2006 occurred there. In South Africa, a total of 5.5 million people, including 240,000 children younger than 15 years, were living with HIV in 2005. HIV data gathered in the country’s antenatal clinic surveillance system suggest that HIV prevalence has not yet reached a plateau. There is a continuing trend nationally in HIV infection levels among pregnant women attending public antenatal clinics: from 22.4% in 1999 to 30.2% in 2005 (a 35% increase). Aim: The aim of this study was to assess sexual practices, the prevalence of condom usage and sexually transmitted diseases, and their associations among 930 men and women aged 15-60 years in Orange farm South Africa. Objectives: 1. To determine condom usage among males and females aged 15–60 year old. 2. To determine the number of new partners, short-term partners and unprotected sexual acts in this particular age group of men and women. 3. To assess the prevalence of sexually transmitted diseases in this age group. 4. To assess the relationship between sexual practices and sexually transmitted diseases in this community. Methods: The project was a secondary data analysis of a population-based, cross-sectional study was conducted in Orange Farm, South Africa in 2002. The original study involved 930 men and women respondents. A two-stage random sampling technique was used to select households. A self-weighting random sample of twenty households was chosen from clusters of 15 households. All men and women aged 15 to 60 years, who slept in the selected households the night before the study team’s visit, were eligible for inclusion in the study. The main focus of this secondary study was to analyze the baseline data collected for the level and risk factors for sexually transmitted diseases in this age group. All 930 men and women were included in the analysis. Results: The risk factor under consideration viz: condom usage was not optimal, and the prevalence of sexually transmitted disease is high in this population with HIV prevalence at 21.8%. Women in the age-group 15-24 years were disproportionately more affected by HIV in this community as compared to men. Among the HIV positive respondents, 61.8% had at least single or over 2 non-spousal partners in the last year. At the time of the interviews, 34.7% had never used condoms and 84.3% did not use condoms in any of the sexual episodes of the last month. Conclusion: An important goal is to practice partner reduction and to encourage especially those who are single to use condoms consistently. Further qualitative research on sexual behaviours involving focus group discussions, in-depth interviews or participant observation should be conducted in this community to complement the quantitative methods. They produce results that directly represent how people feel and provide information on behaviour through the observation of events and activities.
Keywords: sexual practices; sexually transmitted diseases; Orange Farm; South Africa